Pendampingan "Integrated Programming English” Dalam Pembelajaran Bahasa Inggris - Syarfina, T.; Thyrhaya Zein, T.; Ganie, Rohani; Silvana Sinar, T. (Journal of Community Research and Service, 2025)
The "Integrated Programming English" program aims to improve multimodal literacy, includingprogramming-based English language skills, among students and teachers at MTs SKB 3 Minister Sinar Serdang. Thisprogram involves practical training using lecture methods, demonstrations, simulations and interactive exercises.Through a project-based approach with the Scratch platform, participants are trained to combine language andtechnology skills to solve problems and express themselves creatively. The results of the training showed an increasein participants' motivation to learn English, independence, and language and programming skills. Participants becomemore critical and independent in using technology, increase creativity, and strengthen their ability to work in teams.The positive response to this modern learning method also shows that the integration of technology in languagelearning is not only accepted but also recognized as a relevant and interesting innovation for students. This programopens up opportunities for further adoption in other educational environments to support student competence in facingthe digital challenges of the 21st century